Intraaortic balloon pump support during coronary angioplasty. Initial experience - Osterne,Evandro C.V. (1999)
OBJECTIVE: To evaluate the use of the intraaortic balloon (IAoB) in association with coronary angioplasty in high-risk patients. METHODS: Fourteen high-risk patients unresponsive to clinical therapy and with formal contraindication to surgical revascularization were treated by coronary angioplasty, most of which was followed by stenting. All procedures were performed with circulatory support with the IAoB. This study reports the early results and the late findings after 12 months of follow-up. Six patients had multivessel coronary disease; of these, four had left main equivalent lesions and two had unprotected left main coronary artery disease, one of whom had severe "end-vessel" stenosis and the other was a patient with Chagas' disease with single-vessel lesion. Eleven patients had a left ventricular ejection fraction <30%. RESULTS: In 100% of the patients, the procedures were initially successful. Two patients had severe bleeding during the withdrawal of the left femoral sheath. At the end of twelve months, 4 patients were asymptomatic and the others were clinically controlled. There were two late deaths in the 7th and 11th months. CONCLUSION: The combined use of the intraaortic balloon pump and percutaneous coronary angioplasty in high-risk patients with acute ischemic syndromes provides the necessary hemodynamic stability to successfully perform the procedures.